Dynamic actuation of DNA-assembled plasmonic nanostructures in microfluidic cell-sized compartments - Göpfrich, Kerstin; Urban, Maximilian J.; Frey, Christoph; Platzman, Ilia; Spatz, Joachim P.; Liu, Na (Nano letters, 2020)
Molecular motor proteins form the basis of cellular dynamics. Recently, notable efforts have led to the creation of their DNA-based mimics, which can carry out complex nanoscale motion. However, such functional analogues have not yet been integrated or operated inside synthetic cells toward the goal of realizing artificial biological systems entirely from the bottom-up. In this Letter, we encapsulate and actuate DNA-assembled dynamic nanostructures inside cell-sized microfluidic compartments. These encapsulated DNA nanostructures not only exhibit structural reconfigurability owing to their pH-sensitive molecular switches upon external stimuli but also possess optical feedback enabled by the integrated plasmonic probes. In particular, we demonstrate the power of microfluidic compartmentalization for achieving on-chip plasmonic enantiomer separation and substrate filtration. Our work exemplifies that the two unique tools, droplet-based microfluidics and DNA technology, offering high precision on the microscale and nanoscale, respectively, can be brought together to greatly enrich the complexity and diversity of functional synthetic systems.
Gesehen am 12.05.2020